Immunization of bovines using a DNA vaccine (pcDNA3.1/MSP1b) prepared from the jaboticabal strain of Anaplasma marginale - Andrade, G. M. de; Machado, R. Z.; Vidotto, M. C.; Vidotto, O. (New York Acad Sciences, 2004)
Anaplasma is a tick-borne ehrlichial pathogen of cattle that causes the disease, anaplasmosis. In the present study, a total of 11 Anaplasma marginale seronegative calves were assigned into two groups: one immunized (G1, n = 6) and one nonimmunized-control (G2, n = 5). Six calves were immunized by using a DNA vaccine containing the gene of a major surface protein, MSP1b, encoded by the plasmid identified as pcDNA3.1/MSPIb. Calves received three intramuscular inoculations of 100 mug of pcDNA3.1/MSP1b at a 20-day interval. The control group received buffer phosphate at the same schedule as the experimental group. The immune response elicited by immunization with pcDNA3.1/MSP1b was evaluated in mice and calves. Twenty days following initial immunization, specific serum antibody from four BALB/c mice bound MSP1b in inummoblots. Sixty days after the last immunization, all calves were challenged with cryopreserved A. marginale at a dose of 10(4) parasites/mL/animal by intravenous injection. Results of packed cell volume (PCV) and detection of infected erythrocytes in all experimental groups revealed that the decrease of PCV and detection of infected erythrocytes occurred at 28 to 42 days after challenge. Mean temperature values did not increase over 39.85degreesC. Antibodies developed by immunized bovines from G2 were detected 14 days after challenge. MSP1b was characterized during the immunization period and MSP2 was the most predominant polypeptide at the challenge period. DNA of A. marginale was detected in all groups just after challenge by nested PCR assay. It can be concluded that all immunized bovines were partially protected against homologous challenge.
Keywords: Anaplasma marginale; MSPs; DNA; bovines; immunization